Comparative performance of microscopy, rapid diagnostic tests, and multiplex real-time PCR for detection of malaria parasites among pregnant women in northwest Ethiopia - Zemenu Tamir; Abebe Animut; Sisay Dugassa; Araya Gebresilassie; Mahlet Belachew; Adugna Abera; Berhanu Erko (Malaria Journal)
Abstract Background Low malaria parasitaemia is a diagnostic challenge in pregnancy, leading to false negative microscopy and rapid diagnostic test (RDT) results. However, these submicroscopic or subpatent infections could cause adverse pregnancy outcomes. Thus, evaluating the diagnostic performance of microscopy, RDT, and multiplex qPCR in pregnancy is vital for informed decisions. Methods A total of 835 peripheral blood and 372 placental blood samples were collected from 835 pregnant women attending first antenatal care or admitted for delivery at selected health facilities in northwest Ethiopia between November 2021 and July 2022. In multiplex qPCR, all microscopy and/or RDT positive samples were extracted and amplified individually, whereas all samples negative by both RDT and microscopy were extracted after pooling ten samples together and tested for Plasmodium genus. The diagnostic performance of microscopy, RDT, and multiplex qPCR in pregnancy was compared and evaluated against each other. Results Using multiplex qPCR as a reference test, microscopy had a sensitivity of 73.8% (95% confidence interval (CI): 65.9–80.7) and 62.2% (95% CI: 46.5–76.2) to detect Plasmodium parasites in peripheral and placental blood samples, respectively, with a 100% (95% CI: 98.9–100) specificity in both samples. Similarly, the RDT had a sensitivity of 67.6% (95% CI: 59.3–75.1) and a specificity of 96.5% (95% CI: 94.9–97.8) for Plasmodium infection diagnosis in peripheral blood and a sensitivity of 62.2% (95% CI: 46.5–76.2) and a specificity of 98.8% (95% CI: 96.9–99.7) in placental blood samples. Considering microscopy as a reference test, multiplex qPCR showed a sensitivity of 100% (95% CI: 96.6–100) and a specificity of 94.8% (95% CI: 93.0–96.3) to diagnose Plasmodium infections in both peripheral and placental blood samples. Pooled multiplex qPCR detected 34 peripheral and 12 placental blood Plasmodium infections from microscopy and RDT negative samples. The pooled assay obviated about half of the reactions and its testing costs. Microscopy showed almost perfect agreement (κ = 0.823) with multiplex qPCR for detecting malaria parasites in pregnancy, whereas the RDT showed a substantial agreement (κ = 0.684). Conclusion Multiplex qPCR had a better performance for Plasmodium infection diagnosis in pregnancy compared to microscopy and RDT. Pooled multiplex qPCR could be a sensitive and resource-efficient strategy for epidemiological surveillance of Plasmodium infections in pregnancy.